Safety of same‐day discharge after uncomplicated, minimalist transcatheter aortic valve replacement in the COVID‐19 era. Issue 5 (31st December 2020) - Perdoncin, Emily; Greenbaum, Adam B.; Grubb, Kendra J.; Babaliaros, Vasilis C.; Keegan, Patricia; Ceretto‐Clark, Brendan; Wei, Jane; Guyton, Robert A.; Paone, Gaetano; Byku, Isida; Gleason, Patrick T.; Biven, Kelby; et al.
Abstract: Objectives: We sought to evaluate the safety, efficacy and feasibility of same‐day discharge after uncomplicated, minimalist TAVR. Background: At the start of the COVID‐19 pandemic, we created a same‐day discharge (SDD) pathway after conscious sedation, transfemoral (minimalist) TAVR to help minimize risk of viral transmission and conserve hospital resources. Studies support that next‐day discharge (NDD) for carefully selected patients following minimalist TAVR is safe and feasible. There is a paucity of data regarding the safety of SDD after TAVR. Methods: In‐hospital and 30 day outcomes of consecutive patients meeting pre‐specified criteria for SDD after minimalist TAVR at our institution between March and July of 2020 were reviewed. Outcomes were compared to a NDD cohort from July 2018 through July 2020 that would have met SDD criteria. Primary endpoints were mortality, delayed pacemaker placement, stroke and cardiovascular readmission at 30 days. Results: Twenty nine patients were discharged via the SDD pathway after TAVR. 128 prior NDD patients were identified who met all criteria for SDD. The STS scores were similar between the two groups (SDD 2.6% ±1.5 vs. NDD 2.3% ± 1.2). There were no deaths at 30 days in either group. There was no significant difference in delayed pacemaker placement (SDD 0% vs. NDD 0.8%, p > .99) or cardiovascular readmission (SDD 0% vs. NDD 5.5%, p = .35) at 30 days. Conclusions: Same day discharge following uncomplicated, minimalist TAVR in selected patients appears to be safe, achieving similar 30 day outcomes as a cohort of next day discharge patients.